The antimalarial activity of Dicoma anomala and the chloroquine resistance reversing effects of Sclerocarya birrea on Plasmodium falciparum in vitro - Matsabisa, Motlalepula Gilbert (Department of Medicine, 2014)
Includes bibliographical references.